Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/jcs5010002
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Sandwich Composites Manufactured from Recycled Carbon Fibers, Flax Fibers/PP Skins, and Recycled PET Core

Abstract: European union end of life vehicle directive mandates the use of more sustainable/recyclable materials in automotive industries. Thermoplastics matrix-based composites allow recyclability of composites at the end of life; however, their processing technology is more challenging than thermoset composites. Manufacturing process and mechanical testing of sustainable sandwich composite made from sustainable materials: flax, recycled carbon fiber, polypropylene, and recycled PET foam are presented in this article. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Studies have explored utilizing natural fibers in the fabrication of epoxy-based composite structures [ 18 , 19 ]. Studies have confirmed that using flax fibers as a facesheet of sandwich structures can enhance their flexural properties, the results reported contribute to the sustainability of sandwich composites with the usage of natural fibers [ 20 ]. Also, Wagas et al hybridized kenaf and flax fiber as facesheet of sandwich composite structures and studied their impact behavior and it was discovered from their findings that the hybridized facesheet enhanced better energy absorption rate than the glass fiber facesheet [ 21 ].Benjamin et al [ 22 ]also studied the flexural behavior of sandwich structures made with hemp fiber facesheet to bending stress and it was reported from their findings that facesheet made with hemp fibers can enhance the bending strength of sandwich panel [ 22 ].Natural fiber composites hereditably perform poorly in the presence of moisture [ 23 ], affecting the morphology of the natural fiber [ 24 ], crack propagation [ 25 ], and sliding surface reaction [ 25 ].Even with these natural fiber benefits, manufacturing polymer composites with natural fibers is significantly hampered by the incompatibility of the polymer matrix and fiber surface [ 26 ].…”
Section: Introductionmentioning
confidence: 90%
“…Studies have explored utilizing natural fibers in the fabrication of epoxy-based composite structures [ 18 , 19 ]. Studies have confirmed that using flax fibers as a facesheet of sandwich structures can enhance their flexural properties, the results reported contribute to the sustainability of sandwich composites with the usage of natural fibers [ 20 ]. Also, Wagas et al hybridized kenaf and flax fiber as facesheet of sandwich composite structures and studied their impact behavior and it was discovered from their findings that the hybridized facesheet enhanced better energy absorption rate than the glass fiber facesheet [ 21 ].Benjamin et al [ 22 ]also studied the flexural behavior of sandwich structures made with hemp fiber facesheet to bending stress and it was reported from their findings that facesheet made with hemp fibers can enhance the bending strength of sandwich panel [ 22 ].Natural fiber composites hereditably perform poorly in the presence of moisture [ 23 ], affecting the morphology of the natural fiber [ 24 ], crack propagation [ 25 ], and sliding surface reaction [ 25 ].Even with these natural fiber benefits, manufacturing polymer composites with natural fibers is significantly hampered by the incompatibility of the polymer matrix and fiber surface [ 26 ].…”
Section: Introductionmentioning
confidence: 90%
“…Manobala et al [49] compared the thermomechanical behavior of four types of sandwich panels obtained from a combination of flax-reinforced face sheets, glass-reinforced face sheets, coir cores, and PU cores. Jiang et al [50] developed a sandwich panel made of recycled carbon fiber, recycled polyethylene terephthalate (PET) foam, and flax fibers as a good candidate for use in the automotive industry.…”
Section: Sandwich Structures Made Of Non-wood Cellulose Natural Fibersmentioning
confidence: 99%